2016
DOI: 10.1542/peds.2015-4698
|View full text |Cite
|
Sign up to set email alerts
|

Linear Growth and Child Development in Burkina Faso, Ghana, and Malawi

Abstract: We aimed to produce quantitative estimates of the associations between 4 domains of child development and linear growth during 3 periods: before birth, early infancy, and later infancy. We also aimed to determine whether several factors attenuated these associations. METHODS:In 3700 children in Burkina Faso, Ghana, and Malawi, growth was measured several times from birth to age 18 months. At 18 months, language, motor, socioemotional, and executive function development were assessed. In Burkina Faso (n = 1111)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…However, we would expect that any bias introduced by the supplementation would tend to decrease rather than increase the magnitude of the associations and therefore our general conclusions regarding consistent significant predictors would not change. For example, in Malawi and Ghana, we found that maternal LNS attenuated the association of linear growth with motor and language scores (Prado, Abbeddou, Adu‐Afarwuah et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…However, we would expect that any bias introduced by the supplementation would tend to decrease rather than increase the magnitude of the associations and therefore our general conclusions regarding consistent significant predictors would not change. For example, in Malawi and Ghana, we found that maternal LNS attenuated the association of linear growth with motor and language scores (Prado, Abbeddou, Adu‐Afarwuah et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…grows rapidly [43]. In a previous study in the same area, child's length at 6 months of age was associated with language and motor scores at 18 months of age [44].…”
Section: Discussionmentioning
confidence: 75%
“…Prado and colleagues have previously used a language inventory in Ghana. 24 Given the importance of cognition as part of mental development, we added cognitive items and some language items to ones already included in other measures. 4,13 As expected, older, taller children and children with higher scores on a stimulation measure attained higher milestone scores.…”
Section: Mental Development and The Ghana Milestones Measurementioning
confidence: 99%